Prevalence of Dental Caries in Children in Mymensingh and Its Associated Risk Factors: A Cross-Sectional Study - Sharmin Sultana; Mst. Sonia Parvin; Md. Taohidul Islam; Emdadul Haque Chowdhury; A. S. Mahfuzul Bari (MDPI AG, 2022)
Background: Children suffer from various oral and periodontal diseases. Dental caries is one of the most prevalent oral diseases among children in the world. This study was conducted to identify the prevalence and risk factors of dental caries in children in Mymensingh, Bangladesh. Methods: A cross-sectional study was conducted on 362 pediatric patients who attended the Dental Unit of Mymensingh Medical College from March to September 2019. The sample size was calculated using a statistical formula and the children were selected using a systematic random sampling technique. Children and their guardians were interviewed and data were recorded using a structured questionnaire. Risk factors were analyzed using multivariate logistic regression. Results: The overall prevalence of dental caries was 82.7%. The prevalence of caries was significantly higher in aged children (8-10 years) and also in rural, low-income, and illiterate families. Seven significant risk factors were identified that included residence in the rural area (OR: 7.31 [1.73-30.83]), a parental income of BDT ≤ 20,000 per month (OR: 4.75 [1.49-15.05]), reduced duration (≤1 min) of teeth cleaning (OR: 18.54 [2.05-168.17]), teeth cleaning before breakfast (OR: 93.30 [10.95-795.32]), the spoon-feeding method (OR: 12.57 [2.09-75.61]), long-term (37-48 months) breastfeeding (OR: 212.53 [8.69-5195.25]), and family oral problem (OR: 8.20 [2.57-26.16]). Conclusions: The prevalence of dental caries among the children in Mymensingh is very high and was associated with residence in rural areas, parental income, reduced duration of teeth cleaning, teeth cleaning before breakfast, the spoon-feeding method, long-term breastfeeding, and family oral problems.